Providing compensation for patients with diseases who cannot be given the COVID-19 Vaccine - Yamin, Muhammad; Hidayat, Yusuf; Sadino, Sadino (Gema Wiralodra, 2023)
This study aims to describe the procedures and barriers associated with compensating disease sufferers who are not eligible to receive the COVID-19 vaccine. The research method used is normative research, which focuses on analyzing legal aspects based on legal regulations, including Presidential Regulation Number 99 of 2020, concerning Procurement of Vaccines and Implementation of Vaccinations in the Context of Overcoming the 2019 Coronavirus Disease (COVID-19) Pandemic, as well as regulations other relevant matters. Research data was obtained through literature study and document analysis, including primary and secondary legal materials. Data analysis was carried out descriptively and qualitatively with a deductive approach, which refers to general legal principles. The research results identified various obstacles, including technical problems such as a lack of public discipline in undergoing health checks before receiving vaccination and a lack of compliance from medical personnel who manage vaccination procedures per established guidelines. As a result, some groups of people who should not receive the COVID-19 vaccine still receive vaccination, which can ultimately cause side effects. The research also highlights Presidential Regulation Number 14 of 2021 concerning Procurement of Vaccines and Implementation of Vaccinations in the Context of Overcoming the COVID-19 Pandemic, which provides compensation guarantees following applicable regulations if a Post-Vaccination Adverse Event (AEFI) occurs which has the potential to cause disability or death in sufferers of the disease who are not eligible to receive the COVID-19 vaccine. The results of this research provide a deeper understanding of the challenges and obstacles in implementing COVID-19 vaccination, especially in the context of disease sufferers who do not meet the requirements to receive the vaccine, as well as the importance of guaranteeing compensation in AEFI situations that have the potential to have profound impacts.